Experimental study of the effect of variation in in-situ stress on capillary residual trapping during CO2 geo-sequestration in sandstone reservoirs - Saeedi, Ali; Rezaee, M. Reza; Evans, Brian (Blackwell Publishing, 2012)
During a geo-sequestration process, CO2 injection causes an increase in reservoir pore pressure, which in turn decreases the reservoir net effective stress. Changes in effective stress can change all the reservoir and cap-rock properties including residual saturations. This article presents the results of an experimental work carried out to understand the potential change in the volumes of residually trapped CO2, while the porous medium tested underwent change in the net effective stress under in-situ reservoir conditions of pore pressure and temperature. The experimental results obtained show that an initial 1725 psi (11.9 MPa) decrease in the net effective pressure caused 1.4% reduction in the volumes of residually trapped CO2, while another 1500 psi (10.3 MPa) reduction caused a further 3.2% drop in the residual saturation of CO2.